2020
DOI: 10.1136/bmjopen-2020-037012
|View full text |Cite
|
Sign up to set email alerts
|

National survey to estimate sodium and potassium intake and knowledge attitudes and behaviours towards salt consumption of adults in the Sultanate of Oman

Abstract: ObjectivesTo estimate population sodium and potassium intakes and explore knowledge, attitudes and behaviour (KAB) towards the use of salt in adults in the Sultanate of Oman.DesignNational cross-sectional population-based survey.SettingProportional random samples, representative of Omani adults (18 years or older), were obtained from all governorates of the Sultanate of Oman.ParticipantsFive hundred and sixty-nine (193 men, 376 women; 18 years or older) were included in the analysis (response rate 57%). Mean a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Spot urine samples were collected from the participants who were asked to collect a sample in the evening before fasting, which was brought to the appointment for blood testing the next morning. Sodium levels in the urine samples were determined using an ion-selective electrode with Abbott Architect c8000 & Roche Cobas 6000 analysers [ 12 ]. Quality control measures were taken by each of the health centre laboratories’ analysers to ensure accurate results.…”
Section: Methodsmentioning
confidence: 99%
“…Spot urine samples were collected from the participants who were asked to collect a sample in the evening before fasting, which was brought to the appointment for blood testing the next morning. Sodium levels in the urine samples were determined using an ion-selective electrode with Abbott Architect c8000 & Roche Cobas 6000 analysers [ 12 ]. Quality control measures were taken by each of the health centre laboratories’ analysers to ensure accurate results.…”
Section: Methodsmentioning
confidence: 99%
“…Our study found that the median daily salt intake was 10.5(7.3-15.1) gm/day which was similar to the previous reports and is similar to that from other countries in the Arabian gulf region. 19,22 The median salt intake of women in our study is higher than that of the men. This is contrary to many other studies which found the salt intake in males to be more than females.…”
Section: Discussionmentioning
confidence: 51%
“…26 Awareness regarding the dangers of salt intake in our study was high, as reflected in other recent studies from the region. 22,27 However this did not translate into actual reductions in the amount of salt consumed. We found that the youngest age group (18-28 years) had the lowest salt intake compared to other two groups, although on the practices questionnaire, they were less likely than the older group to take actions to reduce salt.…”
Section: Discussionmentioning
confidence: 99%
“…As the habitual potassium intake in most countries worldwide is low [ 6 , 40 , 45 , 46 , 47 , 48 ], an average increase of approximately 40% per day (as found in our meta-analysis) would lead to the achievement of the target of approximately ~4500 mg/day (~90 mmol/day of urinary excretion). Notably, these results also suggest a better effect of potassium supplementation at lower salt intake and, considering the high salt consumption in most countries in the world [ 45 , 46 , 47 , 49 , 50 ], also an associated low salt diet would lead to a reduction of the risk.…”
Section: Discussionmentioning
confidence: 53%